Formation of a meltable purinate metal–organic framework and its glass analogue. Issue 6 (21st December 2022) - Bumstead, Alice M.; Castillo-Blas, Celia; Pakamorė, Ignas; Thorne, Michael F.; Sapnik, Adam F.; Chester, Ashleigh M.; Robertson, Georgina; Irving, Daniel J. M.; Chater, Philip A.; Keen, David A.; Forgan, Ross S.; Bennett, Thomas D.
Abstract : We find that a novel purine-containing framework has one of the lowest melting temperatures recorded for a ZIF. Abstract : The chemistries that can be incorporated within melt-quenched zeolitic imidazolate framework (ZIF) glasses are currently limited. Here we describe the preparation of a previously unknown purine-containing ZIF which we name ZIF-UC-7. We find that it melts and forms a glass at one of the lowest temperatures reported for 3D hybrid frameworks.